Monitoring physiological responses and fluid balance of elite female beach handball players during an international tournament - Ceylan, B.; Kerem, M. K.; Çeyiz, S. C.; Gürses, V. V. G.; Akgül, M. S. A.; Baydil, B. B. (Physical Education of Students, 2020)
Background and Study Aim. Despite its increasing popularity, beach handball has not been studied in terms of physiological responses. Thus the aim of this study was to demonstrate lactate and heart rate responses as well as urine specific gravity (USG) levels and fluid intakes of female university students who competed at an international beach handball tournament. Material and Methods. Five university students who are also handball players (age: 21±1,2, body weight: 56,6±6,4, height:1,61±0,06 and BMI: 21,7±1,43) voluntarily participated in this study. Heart rate (HR), lactate level (LA) and USG were measured before each and immediately after each competition and fluid intake during competition was monitored. Results: The mean values of lactate accumulation and heart rate before and after the match were 1,4 mmol and 87,3, 5,0 and 123,9, respectively. Athletes were euhydrated before the matches (USGmean=1,018) and only presented dehydration after the second match. Conclusions. Beach handball does not result in strenuous physiological effects according to heart rate and lactate responses. Their fluid intake was not enough to eliminate dehydration. Despite fluid availability during the match they presented dehydration at the second match.